Social and Environmental Mobilization in the Arctic: Exploring the Discursive Strategies of the Gwich'in People - Jurčová, Alžběta (Univerzita Karlova, Fakulta sociálních věd, 2023)
This thesis explores the discursive practices of the Gwich'in tribe in Alaska, specifically in the context of the environmental conflict over the proposed oil development in the Arctic National Wildlife Refuge, an area they have inhabited for generations. Over the years, the tribe has been actively engaged in political activism to protect the Refuge from oil development, with a specific focus on safeguarding the Porcupine Caribou herd that inhabits the area. Drawing upon the theoretical framework of political ecology, the thesis posits that the core of this conflict lies in differing ontologies of nature rather than divergent interests. To address this research problem, the thesis investigates the discursive strategies employed by the Gwich'in and their evolution, utilizing critical discourse analysis guided by Van Dijk's sociocognitive approach. By analyzing testimonies given by Gwich'in speakers before the US Congress between 2003 and 2019, the research identifies four key discursive strategies utilized by the Gwich'in. The empirical evidence supports the hypothesis that ontological differences underpin the tribe's discursive repertoire. Through an exploration of the Gwich'in tribe's discursive practices, the thesis seeks to gain deeper insights into how their discursive practices contribute to. Diplomová práce zkoumá diskurzní praktiky kmene Gwich'in, a to konkrétně v kontextu environmentálního konfliktu týkajícího se plánované těžby ropy v Arktické národní přírodní rezervaci, kterou kmen obývá již generace. Gwich'in se dlouhodobě aktivně zapojují do politického aktivismu za ochranu rezervace před těžbou ropy, a v rámci své kampaně kladou zvláštní důraz na ochranu stáda karibů, které oblast obývá. Teoretický rámec práce vychází z poznatků politické ekologie a předpokládá, že jádro tohoto konfliktu spočívá v různých ontologiích přírody, nikoli v rozdílných zájmech obou stran konfliktu. Za účelem řešení tohoto výzkumného problému se práce ptá, jaké diskurzní strategie Gwich'in používají a jak se tyto ...